The Influence Of School Environment On Student Character Formation - Napitupulu, Rio Parsaoran; Sihombing, Lisbet N; Pasaribu, Eva Pasarib; Purba, Nancy A (Jurnal Ilmu Sosial Mamangan, 2024)
The purpose of this study was to find out whether there was an influence from the school environment on the character formation of fifth grade students at UPTD SD Negeri 122371 Pematangsiantar T.A 2023/2024. The results  of the calculations are distributed to respondents, namely class V students. Through the t hypothesis test that t and Sig which describe that the school environment (variable X) is at 0.01, which means it is smaller than 0.05, this indicates that there is a significant influence on the school environment (x) with Character Formation (y). where tcount 2.608 > ttable 2.04, so there is a significant influence of variable x on variable y while in R Square a value of 0.559 is obtained, meaning that the magnitude of the independent variable (x) in explaining the dependent variable is 53.7% while the remaining 44.4% is influenced by other variables such as the contextual approach to the character building of fifth grade elementary school students.